1988
DOI: 10.1111/j.1365-2044.1988.tb04147.x
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac sodium for post‐tonsillectomy pain in children

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 6 publications
1
36
0
2
Order By: Relevance
“…All these agents have the potential to increase the incidence of postoperative bleeding. Diclofenac was found to be effective in reducing posttonsillectomy pain although increasing the incidence of the postoperative bleeding [20]. Despite the use of many medications, pain is still one of the most important morbidities of tonsillectomy.…”
Section: Discussionmentioning
confidence: 98%
“…All these agents have the potential to increase the incidence of postoperative bleeding. Diclofenac was found to be effective in reducing posttonsillectomy pain although increasing the incidence of the postoperative bleeding [20]. Despite the use of many medications, pain is still one of the most important morbidities of tonsillectomy.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly important because agents without respiratory depressant effects, such as non-steroidal antiinflammatory drugs, acetaminophen, and local anesthetics, while used, are often inadequate to treat postoperative tonsillectomy pain. [4][5][6][7][8][9] Dexmedetomidine, a selective a 2 adrenoreceptor agonist with sedative and analgesic properties and without respiratory depressant effects, was shown to have similar effects on post-tonsillectomy opioidrescue needs as did higher doses of morphine. 10 More recently, researchers also showed that an intraoperative infusion of dexmedetomidine reduces the proportion of patients requiring morphine rescue during the postoperative period after tonsillectomy.…”
Section: Résumémentioning
confidence: 99%
“…[30,31]. Des Weiteren können eine opioidbedingte Sedierung und Atemdepression mit folgeschweren Komplikationen insbesondere nach Ein griffen im Pharynx einhergehen; hier ist eine rasche Wiederkehr der Luftwegsre flexe erwünscht [32,33]. Die Association of Paediatric Anaesthetists of Great Bri tain and Irland (APAGBI) empfiehlt die intraoperative Gabe von Opioiden und die perioperative regelmäßige Verabrei chung von NSAR und/oder Paracetamol bei Kindern mit Tonsillektomieschmer zen [34].…”
Section: Postoperatives Erbrechenunclassified